2021
DOI: 10.1177/0020764021991896
|View full text |Cite
|
Sign up to set email alerts
|

Mental health impact of the Covid-19 pandemic on parents in high-risk, low income communities

Abstract: Background: COVID-19 has spread across the globe, resulting in significant changes in virtually every aspect of life. Mitigation efforts, like shelter-in-place orders, have taken a particular toll on parents who have had to navigate disruptions in work and/or school schedules. Research from high-income countries demonstrates increased parental anxiety, stress, depression, and burnout resulting from the pandemic. It is unclear if these outcomes are the same for parents in high-risk communities in low-income cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 28 publications
2
37
0
2
Order By: Relevance
“…Nach internationalen Studien scheint das Auftreten von erhöhtem elterlichen Stress und Belastung ein weltweites Phänomen während der Pandemie zu sein (z. B. im Vereinigten Königreich [15], in den USA [12][13][14], in Italien [16,17] und in Guatemala [18]), wobei ein höheres Stressniveau mit einem jüngeren Alter von Eltern und Kindern assoziiert war.…”
Section: Statistische Analysenunclassified
See 1 more Smart Citation
“…Nach internationalen Studien scheint das Auftreten von erhöhtem elterlichen Stress und Belastung ein weltweites Phänomen während der Pandemie zu sein (z. B. im Vereinigten Königreich [15], in den USA [12][13][14], in Italien [16,17] und in Guatemala [18]), wobei ein höheres Stressniveau mit einem jüngeren Alter von Eltern und Kindern assoziiert war.…”
Section: Statistische Analysenunclassified
“…Im Vergleich zu Kindern wurde die elterliche Gesundheit allerdings während der COVID-19-Pan- demie bisher weniger intensiv erforscht. Erste nationale [9][10][11] und internationale [12][13][14][15][16][17][18] Ergebnisse deuten jedoch darauf hin, dass Eltern von den Pandemiemaßnahmen besonders betroffen sind.…”
Section: Introductionunclassified
“…Furthermore, the general population has been exposed to stressors due to the fear of being infected and the preventive restrictions imposed, which included social distancing, isolation, quarantine, and loss of employment [2]. Such stressors may cause substantial mental health difficulties, especially among vulnerable populations, including the elderly, individuals with chronic diseases, and low-income families [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A study was conducted by Alonzo et al, on mental health impact of the COVID-19 pandemic on parents in high-risk, low-income communities. 14 It showed that parents more often reported feelings of burnout than nonparents (p<0.001) and nonparents were 70% less likely to endorse the feelings of stress when compared to parents (OR=0.285; p=0.014).…”
Section: Discussionmentioning
confidence: 97%